Strategic Planning on Smart Mobility Development - Setyowati, Kristina; Suryawati, Retno; Parwiyanto, Herwan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The increase in population and in vehicles has generated a challenge in urban transportation. Simultaneously, Intelligent Transport System (ITS) technology development has provided urban areas with an opportunity to address transportation challenges. Therefore, a concept of smart mobility is developed, which is derived from smart city concept using ITS development. The objective of research is to organize a Strategic Planning of Smart Mobility. This research used the qualitative descriptive approach. Its data were collected from the city of Surakarta as an implementer of Smart Mobility through in-depth interviewing and content analysis. Data analysis in the first stage was carried out by using the SWOT analysis method to determine strategic issues. The second stage of analysis was aimed to evaluate the strategy by using the litmus test. The results of this research based on the two stages show that strategic plan could be observed from the development of Smart Mobility in Surakarta City and several strategies could be offered and formulated as follows: 1) strategy of developing and improving cooperation with stakeholders; 2) strategy of improving and intensifying the application of e-Gov through ITS application and development; 3) strategy of reinforcing inter-mode integration; and 4) strategy of developing the synchronization of public policy to restrict the number of private vehicles.